Genealogi Penafsiran Bidadari dalam Al-Qur’an: Analisis Wacana Kuasa dalam Tafsir Klasik hingga Kontemporer - Mida Hardianti (Quranic and Tafsir studies Programme at Ushuluddin Faculty, 2025)
This article explores the genealogy of interpretations of the term bidadari (heavenly companions) in the Qur’an from classical to contemporary periods. Using Michel Foucault’s genealogical method and supported by feminist hermeneutics, particularly Amina Wadud’s classification of tafsir, the study investigates how gendered narratives in eschatological verses have evolved over time. Classical exegeses tend to present bidadari as sensual female figures intended as rewards for male believers, reinforcing patriarchal paradigms. In contrast, contemporary interpretations emphasize symbolic and ethical dimensions that are more inclusive and just. By tracing interpretive models—traditional, reactive, and holistic—this study demonstrates how exegetical authority interacts with cultural power structures, producing normative gendered meanings. The analysis also shows how knowledge production in tafsir is embedded in political, religious, and social contexts that marginalize women’s experiences and spiritual agency. Ultimately, this article contributes to Qur’anic gender studies by offering a critical discourse analysis of theological narratives that have long been accepted as absolute. It argues for interpretive renewal that prioritizes justice, reciprocity, and contextual relevance.